DAMPAK MOTIVASI BELAJAR SISWA SD PADA MASA PANDEMI COVID-19 TERHADAP HASIL BELAJAR - Muslim Nurdin; Wati Karmila (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam YAPTIP Chadijah Ismail Pasaman Barat, 2021)
The purpose of this study was to describe the impact of elementary student learning motivation during the Covid-19 pandemic on learning outcomes. This research is a descriptive quantitative study that focuses on evaluating learning using online media. The study population was all students at SD Karangpawitan Garut. While the sample was only 30 students, who were selected using simple random sampling technique taking into account the homogeneity of the population. The data collection instrument used an online learning questionnaire. Data analysis using descriptive statistics. The results illustrate the degree of closeness between motivation and learning outcomes during the pandemic in elementary school children in Karangpawitan Garut can be seen from the value of the contribution (contribution) X1 to Y seen from R = 0.845 and the coefficient of determination (R Square) = 0.715 including in the very strong category. This shows that learning outcomes are influenced by 71.5% of learning motivation. While the remaining 100% - 71.5% = 28.5% is influenced by other variables not examined in this study.